2019
DOI: 10.1029/2019jf005104
|View full text |Cite
|
Sign up to set email alerts
|

Size‐Independent Susceptibility to Transport in Aeolian Saltation

Abstract: Natural wind-eroded soils contain a mixture of particle sizes. However, models for aeolian saltation are typically derived for sediment bed surfaces containing only a single particle size. To nonetheless treat natural mixed beds, models for saltation and associated dust aerosol emission have typically simplified aeolian transport either as a series of noninteracting single particle size beds or as a bed containing only the median or mean particle size. Here we test these common assumptions underpinning aeolian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 78 publications
3
27
0
Order By: Relevance
“…Hence, like Pähtz and Durán (), we hypothesize that u t is the minimal wind shear velocity that is needed to compensate energy losses of rebounding particles during particle trajectories, which is a size‐selective process because larger particles are accelerated less strongly during their hops. Note that the finding of size selectivity does not contradict the field measurements by Martin and Kok (), which showed that the size distribution of particles in saltation is relatively insensitive to the wind shear velocity u * , because the sand beds at these authors' field sites were considerably better sorted ( d 90 / d 50 ≈1.6) than our Samples 5 ( d 90 / d 50 ≈2.2) and 6 ( d 90 / d 50 ≈2.5) and thus likely did not exhibit a significant difference between utvis and utzo (like our Samples 1–4).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Hence, like Pähtz and Durán (), we hypothesize that u t is the minimal wind shear velocity that is needed to compensate energy losses of rebounding particles during particle trajectories, which is a size‐selective process because larger particles are accelerated less strongly during their hops. Note that the finding of size selectivity does not contradict the field measurements by Martin and Kok (), which showed that the size distribution of particles in saltation is relatively insensitive to the wind shear velocity u * , because the sand beds at these authors' field sites were considerably better sorted ( d 90 / d 50 ≈1.6) than our Samples 5 ( d 90 / d 50 ≈2.2) and 6 ( d 90 / d 50 ≈2.5) and thus likely did not exhibit a significant difference between utvis and utzo (like our Samples 1–4).…”
Section: Discussionsupporting
confidence: 68%
“…Hence, like Pähtz and Durán (2018a), we hypothesize that u t is the minimal wind shear velocity that is needed to compensate energy losses of rebounding particles during particle trajectories, which is a size-selective process because larger particles are accelerated less strongly during their hops. Note that the finding of size selectivity does not contradict the field measurements by Martin and Kok (2019), which showed that the size distribution of particles in saltation is relatively insensitive to the wind shear velocity u * , because the sand beds at these authors' field sites were considerably better sorted (d 90 ∕d 50 ≈ 1.6) than our Samples 5 (d 90 ∕d 50 ≈ 2.2) and 6 (d 90 ∕d 50 ≈ 2.5) and thus likely did not exhibit a significant difference between u vis t and u z o t (like our Samples 1-4). In summary, for poorly sorted sand beds, there may be three distinct dynamic thresholds: a threshold associated with the cessation of intermittent saltation transport of relatively fine particles (u vis t ), a larger threshold associated with the cessation of intermittent saltation transport of the entire ensemble of particles (u z o t ), and an even larger threshold below which continuous saltation transport becomes intermittent (there is an ongoing controversy about whether this threshold is associated with splash entrainment or aerodynamic entrainment; .…”
Section: 1029/2019jf005094supporting
confidence: 45%
See 2 more Smart Citations
“…Curiously, the slope of the attrition parameter with grain size does not have a consistent sign across environments. We speculate that negative slopes imply efficient production of dust, if there is equal transport susceptibility of grain-sizes 29 .…”
Section: Impact Thresholdmentioning
confidence: 92%